Predicting Sexual Risk Behavior in British and European Union University Students in the United Kingdom. Issue 1 (2nd January 2021) - Jaspal, Rusi; Lopes, Barbara; Wignall, Liam; Bloxsom, Claire
Abstract: Drawing on the Health Adversity Risk Model, this study examines the relationship between mental health and sexual risk behaviors in British and European Union (EU) university students in the United Kingdom. Four hundred and thirty-one undergraduate students completed a cross-sectional survey. Data were analyzed using independent samples t -tests, multiple regression and structural equation modeling. Results showed that female students and British students exhibited higher levels of psychological distress, self-harm and sexual risk behaviors than males and EU students; and that female and EU students were more likely to adopt adaptive coping styles than male and British students, respectively. The structural equation model suggests that the relationship between gender and citizenship and sexual risk-taking is mediated by identity threat, psychological distress, coping styles and self-harm. Adaptive coping styles are not necessarily protective against sexual risk-taking but rather determine the type of sexual risk behavior: re-thinking/planning is associated with volitional risk behaviors and social engagement with non-volitional behaviors. Social and cultural norms may shed light on mental health outcomes and sexual risk-taking in university students.